2014
DOI: 10.1159/000368984
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Heterozygosity of PTEN (Encoding Phosphate and Tensin Homolog) Associated with Elevated HER2 Expression Is an Adverse Prognostic Indicator in Gastric Cancer

Abstract: Objective: PTEN (the encoding phosphate and tensin homolog) is a well-known cancer suppressor gene and its mutation and loss of heterozygosity (LOH) occurs in various types of carcinomas. This study aimed to examine the association between LOH of PTEN and prognosis in HER2-expressing and nonexpressing gastric cancer patients. Methods: Fresh-frozen tumor samples of 221 gastric cancer patients with a primary diagnosis of gastric carcinoma were examined for LOH of PTEN. The results were compared with pathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
4
0
1
Order By: Relevance
“…These findings are consistent with those of previous reports in gastric cancer (11-21.5 % with PTEN loss [17][18][19] and 2.5-15.9 % with PIK3CA mutations [18,[20][21][22]). More importantly, as many as 34.5 % of patients with HER2 overexpression who are thought to be candidates for trastuzumab therapy showed PTEN loss, whereas PIK3CA mutations were found in only 5.6 % of these patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with those of previous reports in gastric cancer (11-21.5 % with PTEN loss [17][18][19] and 2.5-15.9 % with PIK3CA mutations [18,[20][21][22]). More importantly, as many as 34.5 % of patients with HER2 overexpression who are thought to be candidates for trastuzumab therapy showed PTEN loss, whereas PIK3CA mutations were found in only 5.6 % of these patients.…”
Section: Discussionsupporting
confidence: 93%
“…Zaitsu et al [19] showed that loss of heterozygosity of PTEN, which results in PTEN deficiency, was associated with HER2 overexpression. However, some reports have shown that loss of PTEN expression or deletion of the PTEN gene is rarely found (3.7-5.3 %) in HER2-overexpressing gastric cancer [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, even in HER2-positive tumors, the antitumor activity of trastuzumab combined with chemotherapy is not always sufficient to extend the survival of gastric cancer patients. Among several markers that are reported to predict sensitivity to trastuzumab, loss of PTEN function is said to be one of the mechanisms of resistance to trastuzumab [42,43] . Taken together, these observations suggest that HER2-expressing cases might be sensitive to the anti-PD-L1 antibody, and PTEN loss may induce PD-1 expression, thus leading to the resistance to trastuzumab in patients with PTEN loss.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the assessment method were previously reported [19,20] . In brief, two microsatellite markers, D10S1765 and D10S1173, were used and PCR amplifications performed as previously described [19] .…”
Section: Loss Of Heterozygosity Of Ptenmentioning
confidence: 99%
“… + + * + + 119 100 Yoda 2015 Japan ? + + * + + 120 101 Zaitsu 2015 Japan + + + * + + 121 102 Lu 2015 China ? + + * ?…”
Section: Resultsunclassified